Soil spiders in differing environments: Eucalyptus plantations and grasslands in the Pampa biome, southern Brazil - LOPES-RODRIGUES, EVERTON NEI; DE S. MENDONÇA, JR, MILTON; L. O. ROSADO, JOÃO; LOECK, ALCI E. (Revista Colombiana de Entomología, 2010)
The Pampa biome in southern Brazil has grassland areas with high biodiversity. Given the fast advance of Eucalyptus silviculture over grassland areas in this biome, and the scant knowledge on the soil spider fauna in these landscapes, we aimed to provide a first view of spiders occurring there and to quantitatively evaluate differences in the spider fauna between the two environments. Study areas included five farms each with the two environments, native grassland and Eucalyptus plantation. Spider densities were 6.53 (±1.01s.e.) individuals/m2  in silviculture and 3.88 individuals/m2  (±0.73) in grassland. This could be due to spiders finding more shelter sites underneath a denser silviculture litter than in the grassland where they could be more exposed, for example, to their own predators. Twenty four spider families were captured; the most abundant and diverse were Salticidae and Linyphiidae. Nineteen families occurred in the silviculture and 21 in the grassland. For adult spiders, 51 morphospecies were determined, the most abundant being Guaraniella mahnerti. Adult abundance was marginally significant for environment, with silviculture areas having more spiders. Species density did not differ between environments or sites, but evenness was significantly higher for the grassland. This better balance in species abundances for spider assemblages in grasslands suggests a healthier environment compared to a monoculture. The most abundant guild was that of the running hunters. Even as a rapid spider diversity inventory, the information gathered here adds considerably to our knowledge on how this new economic upsurge in silviculture affects native environments.